FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO OBESITAS PADA REMAJA DI PANTI ASUHAN DARUN NAJAH SLEMAN YOGYAKARTA - Novi Istanti; Antara, Antok Nurwidi; Ernawati, Yuli (JURNAL KEPERAWATAN, 2024)
Background :Obesity is excess body fat that accumulates and is stored in fatty tissue, causing weight gain. Factors causing obesity in adolescents are genetics, physical activity, lifestyle, health, psychology, poor diet, nutritional intake, duration and quality of sleep, as well as sedentary life style. Objective: to analyze the risk of obesity in adolescents based on physical activity, sleep quality and eating patterns. Method: Quantitative research with a cross sectional approach. The population was 38 teenagers with a sample size of 30t eenagers. Results: Based on the results of the Kendal Tau test, it was found that there was a significant relationship between physical activity, sleep quality and diet (carbohydrate intake and fat intake) with the risk of obesity (p<0.05). Multivariate analysis results showed that’sleep quality factors significantly influenced the risk of obesity (p<0.05). Conclusion: Sleep quality, physical activity, diet (carbohydrate intake and fatintake) are related to the risk of obesity and there are sleep quality factors that influencethe risk of obesity in adolescents (p<0.05).   Keywords: Eating patterns; Physical activity; Sleep quality; Teenagers